Growth spillovers in the MENA region - Merve Aksoylar Baysoy; Sumru Altug (Koç University-TÜSIAD Economic Research Forum (ERF), 2019)
In this paper, we examine the role of spillovers in economic growth for the Middle East and North Africa (MENA) region by accounting for spatial effects. Such spatial effects in growth for the MENA countries may arise on the basis of geography, bilateral trade or institutional similarities. We explicitly model such interactions using a spatial econometric approach and ask how much they are likely to matter for growth externalities and spillover effects. To detect spatial dependence in growth rates, we make of the spatial lag model as well as the model with spatially autocorrelated error terms. Using results from the spatial econometrics literature, we test for the existence and type of spatial dependence. Our results indicate that the economic growth of a MENA country is positively affected by the economic growth of countries that are geographically close and that have similar institutional characteristics rather than through the growth of its trade partners.
Keywords: O40; R11; F43; 330; Growth regressions; spillover effects; spatial econometrics; MENA countries